2019
DOI: 10.1007/s10648-019-09479-z
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Children Become Rejected by Their Peers? A Review of Studies into the Relationship Between Oral Communicative Competence and Sociometric Status in Childhood

Abstract: Being rejected by peers has devastating consequences for a child's future social-cognitive development. It is therefore important to investigate factors that contribute to childhood peer rejection. In doing so, the present review specifically focused on sociometric status, a concept that refers to a child's position within the peer group (e.g., liked or disliked). Although previous studies indicated that children's ability to communicate effectively might partly determine their sociometric status, much was sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 62 publications
(138 reference statements)
0
17
0
2
Order By: Relevance
“…The relation between language problems may be more salient in earlier ages, whereas the role of emotional competence may increase in strength as children become older. A recent review, for instance, found that the relation between language abilities and social problems with peers diminished as children became older [68]. Alternatively, it is possible that emotional competence already mediates the relation between language problems and externalizing problems from an early age, because language is such an important tool in the early emotion socialization process [69,70].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The relation between language problems may be more salient in earlier ages, whereas the role of emotional competence may increase in strength as children become older. A recent review, for instance, found that the relation between language abilities and social problems with peers diminished as children became older [68]. Alternatively, it is possible that emotional competence already mediates the relation between language problems and externalizing problems from an early age, because language is such an important tool in the early emotion socialization process [69,70].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…This might be related to the differences by gender that are often found regarding both interpersonal relations, for example, focusing on acceptance within the group (Andueza and Lavega, 2017), and CLIL (Doiz et al, 2014;Fernandez-Barrionuevo and Baena-Extremera, 2018). Therefore, it is necessary to carry out further research on this topic, because the effects on sociometric measures might need longer to appear (van der Wilt et al, 2019).…”
Section: Discussion Of Qualitative and Quantitative Findingsmentioning
confidence: 99%
“…These findings are consistent with the results of the similar studies in the literature (Bakkaloğlu, Sucuoğlu, & Özbek, 2019;Buysse, Goldman, & Skinner, 2002;Ferreira et. al., 2017;Keane & Calkins, 2004;Koster, Pijl, Nakken, & Van Houten-van den Bosch, 2010;Mand, 2007;van der Wilt, van der Veen, van Kruistum, & van Oers 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%